Feasibility study of a domestic fully automated NAT system for blood screening in blood donors - YAO Fenglan; WANG Rui; HU Jinghui; GE Hongwei; LENG Chan; ZHA Yi; ZHAO Zifu; LIU Zhengmin (Zhongguo shuxue zazhi)
[Objective] To validate the analytical performance, operational performance, and process control measures of a domestic fully automatic nucleic acid testing (NAT) system, thereby ensuring an efficient and orderly blood screening workflow. [Methods] The concordance rate and sensitivity of WanTag-Vortex Plus system were verified using WHO standard reference panels of HIV-1, HCV and HBV, while precision was assessed using weak positive samples of HIV-1, HCV and HBV. As for its operational performance evaluation, cross-contamination resistance was assessed using strong positive samples, and throughput and stress testing were conducted using negative samples. Reagent stability was verified using weak positive samples, and inter-system performance consistency was assessed using verification panels. In addition, the process control measures were verified using the laboratory quality control demand scale. [Results] 1) Verification of concordance rate: The detection results of negative and positive samples of HIV-1, HCV and HBV by WanTag-Vortex Plus system were all consistent with expectations, and the concordance rate was 100%. 2) Precision verification: the repeatability and intermediate precision were extremely high, and the coefficient of variation was less than 5%. 3) Verification of analytical sensitivity: The detection limit of 95% for standard strains of HIV-1, HCV and HBV by WanTag-Vortex Plus system in our laboratory was consistent with the analytical sensitivity provided by reagent manufacturers. 4) Verification of cross-contamination resistance: Five strong positive samples and 87 negative samples were placed according to the actual working conditions and equipment operation design, and the test results were consistent with expectations, with no cross-contamination in the testing system. 5) Throughput and stress testing: Each system completed the individual donor-nucleic acid amplification testing (ID-NAT) of 276 samples in three batches within 12 hours, and successfully completed the ID-NAT test of 828 samples in three consecutive days. 6) Verification of reagent stability: After extreme storage (unsealed storage for 1 week with 4 freeze-thaw cycles), the reagents maintained 100% detection rate in the weak positive samples of HIV-1, HCV, and HBV, showing no significant differences from the control group (Kappa=1). 7) Verification of inter-system performance consistency: The system has stable operation performance, and the performance comparison results across the four devices were consistent (Kappa=1). 8) Process control measures: WanTag-Vortex Plus system software accurately controlled the equipment operation process with strict quality control measures, and correctly interpreted and safely reported the test results. [Conclusion] The analytical and operational performance of the WanTag-Vortex Plus system complies with manufacturer design standards and essential laboratory workflow requirements. Integrated with laboratory information system (LIS), the system's control software meets standard process control requirements, yet requires further improvement.